Scrub typhus, a reemerging zoonosis – An Indian case series - Madi, Deepak; Achappa, Basavaprabhu; Chakrapani, M; Pavan, MR; Narayanan, Saaritha; Yadlapati, Sujitha; Yadlapati, Sujani; Mahalingam, Soundarya (Asian Journal of Medical Sciences, 2014)
Background: Rickettsial diseases are reemerging in many parts of our country. Scrub typhus is a rickettsial disease caused by Orientia tsutsugamushi. It is difficult to diagnose Scrub typhus because of nonspecific clinical presentation and lack of availability of specific tests (ELISA) in all centres. Aim: Our aim was to study the clinical features, lab parameters and outcome of patients diagnosed with Scrub typhus. Materials and Methods: A retrospective hospital based study was done in Mangalore (Karnataka) to identify cases of scrub typhus. Patients who had an acute febrile illness and IgM antibodies against O. tsutsugamushi were included in our study. Results: 10 cases of Scrub typhus were identified. Among them 7(70%) patients were females and 3(30%) were males. Major symptoms on admission were fever10(100%), dyspnea or cough-2(20%), rashes1(10%), altered sensorium1(10%). The major signs were fever10(100%), eschar 2(20%), and signs of meningial irritation in 1(10%). Lab parameters showed leukocytosis in 4(40%), thrombocytopenia in 3(30%), raised liver enzymes in 3(30%) and renal failure in 3(30%). Chest X-ray showed consolidation in 2(20%) patients. There was no mortality in our study. Conclusion: Scrub typhus can present with varying clinical manifestations and eschar can be absent in majority of cases as shown in our study. Therefore diagnosis should be based on a high index of suspicion and empirical treatment with doxycycline must be started whenever there is a strong suspicion of Scrub typhus. Asian Journal of Medical Science, Volume-5(3) 2014: 108-111 http://dx.doi.org/10.3126/ajms.v5i3.9213